Início e circularidade na Ciência da Lógica de Hegel (Revista Eletrônica Estudos Hegelianos, 2021)
In this paper, we reconstruct the debate within the Hegelian studies on what is the most convincing interpretation of the circularity of Hegel’s Logic, which the philosopher presents as a solution to the problem of the logical beginning. Based on the way this problem is presented in the text With what must the beginning of science be made?, in its 1831 version, we reconstruct the debate on the best interpretation of the solution Hegel offers to the problem. This solution is the conciliation of immediacy and mediation in the logical beginning. In addition to reconstructing the debate, we also take a position on it.